Numerical simulation of reinforced concrete shear walls using force-based fiber element method: effect of damping type and damping ratio - Karaton, Muhammet; Osmanli, Omer Faruk; Gulsan, Mehmet Eren (Springer, 2021)
Reinforced concrete shear walls are the structural elements that considerably increase the seismic performance of buildings. Fiber elements and fiber-spring elements are used for the modeling of the inelastic behavior of these elements. The Fiber Element Method provides a certain amount of accuracy for the modeling of reinforced concrete shear walls. However, the studies related to this method are still in progress. In this study, different damping ratios and different damping types used in the structural damping are investigated by using the force-based fiber element method for reinforced concrete shear wall structures. Two shear wall structures subjected to seismic loads are used to compare numerical analysis and experimental results. The comparisons are achieved according to the absolute maximum values of the overturning moment, the base shear force, and the roof displacement. Rayleigh damping and stiffness-proportional damping types for the damping ratios that vary between 2 and 3% provide better results than mass-proportional damping. Additionally, the optimum number of fiber elements for Rayleigh and stiffness-proportional damping types is determined for the optimum damping ratio that provides minimum differences between numerical analysis and experimental results. For these damping types, when the length of a fiber is smaller than 3% of the longitudinal length of the shear wall at the optimum damping ratios, the roof displacement differences between numerical analysis and experimental results are less than 2.5%.
Keywords: Shear wall; Force-based fiber element; Damping types; Damping ratio; Seismic loads